1977
DOI: 10.1084/jem.146.6.1748
|View full text |Cite
|
Sign up to set email alerts
|

The role of H-2-linked genes in helper T-cell function. I. In vitro expression in B cells of immune response genes controlling helper T-cell activity

Abstract: The ability of murine helper T cells primed to the antigen, sheep erythrocytes (SRBC) to cross-react with burro erythrocytes (BRBC) in the in vitro anti-trinitrophenol (TNP) response to TNP-RBC was shown to be under genetic control. Although non-H-2 genes were shown to influence the absolute level of helper activity assayed after SRBC priming, the extent of cross-reaction of SRBC-primed helpers with BRBC was shown to be controlled by an H-2-1inked Ir gene(s). H-2 haplotypes were identified which determined hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
1
1

Year Published

1979
1979
1987
1987

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 47 publications
6
41
1
1
Order By: Relevance
“…There are a number of possible explanations for the expression of lr genes in helper T cells. Many experiments from this (7,(9)(10)(11) and other (8,15,16) laboratories have shown that/r-genes are expressed in B cells and Mth in a manner consistent with the idea that these genes control the recognition of B-cell-or Mth-bound antigen by T cells. By analogy, it may be, as suggested by Zinkernagel et al (17) and von Boehmer et al (5), that/r-genes, expressed in helper T cells, control the recognition of helper T-cell-bound antigen by a second T cell whose activity is required for the response of the helper T cell.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…There are a number of possible explanations for the expression of lr genes in helper T cells. Many experiments from this (7,(9)(10)(11) and other (8,15,16) laboratories have shown that/r-genes are expressed in B cells and Mth in a manner consistent with the idea that these genes control the recognition of B-cell-or Mth-bound antigen by T cells. By analogy, it may be, as suggested by Zinkernagel et al (17) and von Boehmer et al (5), that/r-genes, expressed in helper T cells, control the recognition of helper T-cell-bound antigen by a second T cell whose activity is required for the response of the helper T cell.…”
Section: Resultsmentioning
confidence: 94%
“…Anti-TNP PFC were assayed from triplicate cultures using the slide modification of the hemolytic plaque assay (10). Parallel determinations were made with HRBC and TNP-HRBC and the difference recorded as the number of anti-TNP specific PFC.…”
Section: Assay Of Helper T-cellmentioning
confidence: 99%
See 3 more Smart Citations